2018
DOI: 10.1101/430199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrespect and abuse of women during childbirth in public health facilities in Arba Minch town, South Ethiopia – a cross-sectional study

Abstract: 21Introduction: Disrespect and abuse during childbirth is the main deterring factor to skilled birth 22 utilization as compared to other more commonly known factors such as financial and physical 23 inaccessibility. 24 Objective: To assess the occurrence of women's disrespect and abuse during childbirth in public health 25 facilities in Arba Minch town, south Ethiopia. 26 Methods: Institution based cross-sectional study design was employed at all public health institutions in 27 Arba Minch town, south Ethiopia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 13 publications
4
30
1
Order By: Relevance
“…Freedom from detention is the right of each childbearing woman and a woman or her baby should never be forcibly kept in a facility. Detention is the least reported category by participants, and this is similar to rates reported in other studies from Ethiopia (21,23,25,29,(31)(32)(33) possibly because, maternity services are free of charge in Ethiopia and detention due to unaffordable service bills are rare. The economic status of women has been identi ed as a signi cant barrier to quality care.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Freedom from detention is the right of each childbearing woman and a woman or her baby should never be forcibly kept in a facility. Detention is the least reported category by participants, and this is similar to rates reported in other studies from Ethiopia (21,23,25,29,(31)(32)(33) possibly because, maternity services are free of charge in Ethiopia and detention due to unaffordable service bills are rare. The economic status of women has been identi ed as a signi cant barrier to quality care.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have identi ed that working in under-equipped and overwrought health systems affects provider enthusiasm and is often labelled as signi cant contributor to D&A in facilities (50). Local studies have similarly reported higher incidence of D&A among women who gave birth at hospitals (21,24,25,30,32).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Nine of the included studies were performed simultaneously in both rural-urban settings [ 31 , 35 – 42 ], eleven in urban setting [ 14 , 33 , 34 , 43 51 ] and one in rural setting [ 32 ]. Three of the studies were conducted in the capital (Addis Ababa) [ 33 , 43 , 46 ], two in Tigray region [ 42 , 47 ], four in Amhara region [ 14 , 34 , 44 , 49 ], five in Oromia region [ 36 , 37 , 39 , 50 , 51 ], three in SNNP region [ 38 , 40 , 45 ], two in both SNNP and Amhara regions [ 32 , 35 ], one in four of the regions (Tigray, Oromia, SNNP and Amhara) [ 41 ], and one was done nationwide of rural settings [ 31 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence studies in Ethiopia have shown prevalence reports revealed that women experience at least one form of disrespect and abuse during childbirth ranging from 21.1% [ 32 ] to 98.9% [ 45 ], which are unacceptably high levels of obstetric violence and mistreatment care.…”
Section: Resultsmentioning
confidence: 99%